Development of a Learning Visual Aid for Parabolic Motion in Terms of its Validity and Effectiveness - Rahayu, Mitra; Parrangan, Jeffri; Alfari, Ihang Ramadhan (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study aims to develop a learning aid for the topic of parabolic motion based on air pressure, using a modified 4D development model reduced to 3D. The parabolic motion teaching aids commonly used in schools generally employ manual spring-based launchers, which make it difficult to control the launch velocity. Therefore, this research developed an air pressure-based teaching aid that allows for the adjustment of variables such as launch angle, initial velocity, pressure, maximum height, maximum range, and flight time. The research was limited to the development stage (limited trials) without proceeding to the dissemination phase. The validity of the device was assessed by five validators, consisting of four lecturers and one teacher. The effectiveness of the device was evaluated using response questionnaires administered to 18 students and one physics teacher from Grade XI at SMA Plus Muhammadiyah Merauke in the 2023/2024 academic year. The validity test results showed an average score of 81.2 (81.2%), categorized as very valid, with a minimum validity threshold of 61%. The validation instrument consisted of 20 items. The effectiveness test based on teacher responses yielded a score of 56.72 (76%), categorized as effective, obtained from 10 questionnaire items. Meanwhile, student responses resulted in a score of 43 (86%), categorized as very effective, obtained from 15 questionnaire items. The learning outcome test, consisting of 15 questions, showed an average score of 83.3, with 94% of students achieving scores above the minimum mastery criterion (MMC = 70). Therefore, the air pressure-based parabolic motion teaching aid developed in this study is proven to be highly valid, effective, and feasible for use as a learning medium in teaching parabolic motion.